Silages of sorghum, Tamani guinea grass, and Stylosanthes in an integrated system: production and quality - Prado, Laís Guerra; Costa, Kátia Aparecida de Pinho; da Silva, Luciana Maria; Costa, Adriano Carvalho; Severiano, Eduardo da Costa; Costa, João Victor Campos Pinho; Habermann, Eduardo; e Silva, João Antônio Gonçalves (Frontiers in Sustainable Food Systems, 2023)
Crop–livestock integration systems are efficient technologies for diversifying production and promoting agricultural sustainability. However, less is known about the triple intercropping of crops for silage production. The objective of this study was to evaluate the dry mass production, fermentation profile and nutritive value of the silage of sorghum intercropped with Tamani guinea grass and Stylosanthes cv. Bela in integrated systems. The experimental design was a randomized block with four replicates. The treatments consisted of silage of: 1) sorghum in monocropped; 2) Tamani guinea grass in monocropped (Panicum maximum cv. BRS Tamani); 3) Stylosanthes cv. Bela in monocropped (Stylosanthes guianensis cv. BRS Bela); 4) sorghum intercropped with Tamani guinea grass; 5) sorghum intercropped with Stylosanthes cv. Bela; 6) Stylosanthes cv. Bela intercropped with Tamani guinea grass and 7) sorghum intercropped with Tamani guinea grass and Stylosanthes cv. Bela, totaling 28 experimental silos. Our results showed that sorghum intercropped with tropical forages could be used in integrated silage production systems by increasing the production of silage mass per unit area, providing pasture after crop harvest for silage production, and sustainably improving land-use efficiency. Silage of sorghum intercropped with Tamani guinea grass and Stylosanthes cv. Bela improves the fermentative characteristics and increases the ether extract and total digestible nutrient contents compared with monocropped forage silages. However, tropical forages contribute to increasing the crude protein content of sorghum silage in monocropped, which can result in cost reduction with the acquisition of protein salts to supply protein to ruminant feed. Thus, triple intercropping of sorghum, Tamani guinea grass and Stylosanthes cv. Bela is recommended for silage production and is advantageous for the production of annual and tropical forage crops.